ANALISIS RUGI DAYA PARTIAL DISCHARGE SECARA ONLINE PADA GENERATOR-101 DI PLTP DIENG - Arrad Ghani Safitra; Lovyta Putri Adianti; Andini Pradita; Ismanto, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Partial discharge (PD) is a phenomenon that often occurs in generators and can cause serious damage to equipment and electrical systems one of them at the PLTP PT Geo Dipa Energi (Persero) Dieng Unit. This study aims to investigate partial discharge on generators using the Montesto 200 device. After calculating the power loss due to partial discharge, it can be seen that the largest power loss value occurs in L3 winding with a power loss value of 12,65 Watt. The power loss value will continue to increase if the pulse magnitude value of the partial discharge also increases.